THE EFFECT OF THE ENVIRONMENTAL EXPLORATION APPROACH ON CURIOSITY, CRITICAL THINKING SKILLS, AND SCIENCE LEARNING OUTCOMES - Annisa Cahya Rahayuningtyas; Budi Utami; Annisa Nur Khasanah (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2023)
The natural environment around students can become a learning object that provides students with real experiences. This research aims to determine the effect of the Exploring the Natural Environment (JAS) approach on (1) students' curiosity, (2) students' critical thinking skills, and (3) student learning outcomes. This research uses a quasi-experimental design. The population consists of seventh-grade junior high school students. Data collection techniques are carried out using tests and observations. Prerequisite tests are carried out using validation tests, homogeneity tests, and normality tests. The hypothesis analysis technique is carried out using the independent simple t-test. The research results obtained are, One, there is an influence of the JAS approach on students' curiosity with a sig-2tailed result of 0.011 ? 0.05, Two, there is no influence of the JAS approach on students' critical thinking skills with a sig-2tailed result of 0.080. This is because students still do not fulfill the six categories of critical thinking according to Facione, Three, there is an influence of the JAS approach on student learning outcomes with a sig-2tailed result value of 0.003 ? 0.05. This research concluded that the natural exploration approach (JAS) had an influence on students' learning outcomes and curiosity, but had no effect on students' critical thinking skills. The obstacle in this research is that the time used is still very limited, so better time management is needed.